The Function and genesis of the musical instrument “trombita” with special focus on the Hutsul region - Cząstka-Kłapyta, Justyna Małgorzata (Balcanica Posnaniensia. Acta et studia, 2017)
<span style="color: black; font-family: 'Verdana','sans-serif'; font-size: 7.5pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi;" lang="EN-US">The question of the origins and cultural impact of music cultivated by the Vlachs on the Carpathian music heritage is relatively poorly examined in the previous literature. This is mostly because of insufficient ethno-historical data sources, the short time of detailed documentation of rural folklore, and the collective character of music, which often goes beyond the boundaries of nationality. Most of the previous works dealing with the problem of the Vlachs’ impact on the Carpathian music folklore were presented as a short comments. One of the still unresolved issues is the origin of the shepard’s trumpets (trombitas, horns) in the territory of the Carpathians. It is widely known as “trombita” (the Western Carpathians, Poland), „trembita” (the Ukrainian Carpathians), „trubyela”, „bucium”, and „tulnic” (Romania). They are among the wide type of instruments known by ancient Slavs. According to principal hypothesis these instruments originated in Asia and were transferred to the Carpathian Mountains by migrating Indo-European peoples. Alternative hypothesis suggests that “trembita” was brought to the Carpathians by migrating Roman legionaries, who used this instrument for the signaling functions. The occurrence of these instruments coincides clearly with the area of the Wallachian settlement, allowing the presupposition that the spread of trombita in the Carpathians is linked with the Wallachian colonisation. The problems outlined in this article concerns the spatial distribution and typology of Carpathian trumpets as well as their functions with special focus on the Hutsul region (the Eastern Carpathians, Ukraine), where they still perform important ritual and magical functions, mainly during carolling. The analysis of the function of trombita in this context allows to define its place and importance in the pastoral tradition.